Thermal radiation effect on Unsteady MHD Rear Stagnation Point in AL2O3-Cu/H2O Hybrid Nanofluids - Nurul Amira Zainal,; Iskandar Waini,; Najiyah Safwa Khashi’ie,; Roslinda Nazar,; Pop, Ioan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The evaluation of high thermal efficiency has garnered considerable interest in the context of the unique properties demonstrated by hybrid nanofluids. Therefore, the present study investigates the impact of heat radiation on the unsteady rear stagnation point magnetohydrodynamic (MHD) flow of hybrid nanofluids. The utilisation of similarity transformations allows for the conversion of differential equations with several variables into a specific class of ordinary differential equations. The mathematical model is solved with the bvp4c function. The findings suggest that the unsteady rear stagnation MHD flow in hybrid nanofluid exhibits enhanced heat transfer properties compared to both nanofluid types. The augmentation of nanoparticle concentration and the influence of suction are discovered to have a positive effect on the skin friction coefficient. As the thermal radiation parameter is elevated, a concomitant reduction in the rate of heat transmission is observed. Furthermore, the findings illustrate the presence of two distinct solutions within a particular range.